Studi Literatur Tentang Jenis dan Penyebab Gangguan pada Saluran Transmisi - Khoirunnisa, Nabila; Nelli Inayah; Farid Wiherdiansyah; I Kadek Dwi Adyano; Didik Aribowo (SURYA TEKNIKA, 2024)
Power transmission lines play an important role in distributing electrical energy from power plants to consumers. The reliability of transmission lines is very important to ensure a stable and safe electricity supply. However, various disturbances often occur in transmission lines, both caused by external and internal factors, which can disrupt the operation of the electric power system. This study aims to conduct a literature study on the types of disturbances that occur in transmission lines and identify the causative factors. The method used in this study is a literature study by analyzing various references from books, scientific journals, research reports, and relevant articles. This study identifies several main types of disturbances, such as disturbances due to lightning, strong winds, heavy rain, overload, component failure, and human error. Environmental factors, such as extreme weather and interaction with vegetation, are also common causes of disturbances in transmission lines.